Developing the Vocabulary Mastery of Students through Educational Games - Hasbiyah Srianah Amir; Utary Rustam; Ruslan Hasyim (Qalam : Jurnal Ilmu Kependidikan, 2023)
Abstract It is well known that educational game is able to develop English language skills of children in an attractive way. It can reduce boredom and increase the student’s interest in teaching and learning activities. It can also make learning process more enjoyable. This research aimed to find out the effect of educational games in developing student’s vocabulary mastery of eight years’ students of SMP Negeri 2 Parepare. This research applied pre-experimental method. The result of pre-test and post-test shows that the student’s vocabulary mastery improved significantly. It is shown from the mean score of pre-test was 65.4 and post-test was 79.4. The result of t-test value (10.294) was higher than t-table value (1.685). It concludes that the use of educational games can develop students’ vocabulary mastery.   Keywords: developing, vocabulary mastery, educational games